SIP-TELEPHONY IMPLEMENTATION FOR MOBILE DEVICES POWERED BY ANDROID OPERATING SYSTEM (Modern information system and technologies, 2018)
In the article the analysis of existing solutions Internet telephony for the Android operating system with the purpose of the application of SIP-telephony for Android.